Peran Pendampingan Sosialisasi Sistem Tanggap Darurat Bencana Sebagai Upaya Mitigasi Tanah Longsor di RW 06 Kelurahan Cimahpar - Vivi Permata Sari; Aji Hermawan; Sugeng Heri Suseno; Danang Aria Nugroho (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Landslides are one of the natural disasters that occur due to shifting movement of soil and other rock material. Factors that cause landslides are unsupportive soil structures and additional burdens on human activities that cause the carrying capacity and soil resistance to decrease. The community in RW 06 Kelurahan Cimahpar is an area prone to landslides, in 2019 there have been at least four houses affected by the disaster. RW 06 Cimahpar area is an area that is crossed by a river, and many residents are building houses on landslide prone structures. The socialization of the landslide emergency response system aims to provide knowledge to the community in order to minimize the adverse impacts caused by the disaster, and to mitigate the disaster.